The wandering mind : what medieval monks tell us about distraction - Kreiner, Jamie, 1982- (Liveright Publishing Corporation, a division of W. W. Norton & Company, Independent Publishers Since 1923, 2023)
"A revelatory account of how Christian monks identified distraction as a fundamental challenge, and how their efforts to defeat it can inform ours, more than a millennium later"--